2011
DOI: 10.1103/physrevd.84.064006
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary regime for quasinormal modes of the charged Vaidya metric

Abstract: We consider non-stationary spherically symmetric $n$-dimensional charged black holes with varying mass $m(v)$ and/or electric charge $q(v)$, described by generic charged Vaidya metrics with cosmological constant $\Lambda$ in double null coordinates, and perform a comprehensive numerical analysis of the fundamental quasinormal modes (QNM) for minimally coupled scalar fields. We show that the "instantaneous" quasinormal frequencies exhibit the same sort of non-stationary behavior reported previously for the four… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…In [22], the quasi-normal modes of a scalar field in an electrically charged Vaidya background were studied using a similar numerical setup to what we are going to use here. An interesting investigation done in [22] tried to determine what would happen with the quasi-normal modes as the time-dependent background approached a naked singularity, but the numerical code used was not suitable for following the field evolution after the extremal configuration (q = m) was reached. In our present work, we have a static configuration that describes a naked a singularity in order to study the properties of the quasinormal modes.…”
Section: The Naked Singularity For the Small Wave Mode Numbers -mentioning
confidence: 99%
“…In [22], the quasi-normal modes of a scalar field in an electrically charged Vaidya background were studied using a similar numerical setup to what we are going to use here. An interesting investigation done in [22] tried to determine what would happen with the quasi-normal modes as the time-dependent background approached a naked singularity, but the numerical code used was not suitable for following the field evolution after the extremal configuration (q = m) was reached. In our present work, we have a static configuration that describes a naked a singularity in order to study the properties of the quasinormal modes.…”
Section: The Naked Singularity For the Small Wave Mode Numbers -mentioning
confidence: 99%
“…Our framework is general enough to cover metrics of the Kerr-Schild form. Thus, our approach could be applied in the numerical analysis of quasi-normal modes in Vaidya [14], and more generally, in time-dependent non-axisymmetric Kerr-Schild spacetimes.…”
Section: Arxiv:11092513v3 [Gr-qc] 10 Feb 2014mentioning
confidence: 99%
“…In reference [27] the author considered a time dependent potential and showed that the tail behavior actually changes from the standard time independent potential. This phenomena was also considered in references [28] where the authors considered a Vaidya spacetime where the explicit change in the parameters of the black hole is reflected in the quasi normal frequencies of the scattered field.…”
Section: Discussionmentioning
confidence: 91%